The real effects of share repurchases - Almeida, Heitor; Fos, Vyacheslav; Kronlund, Mathias (Journal of Financial Economics, 2016)
We employ a regression discontinuity design to identify the real effects of share repurchases on other firm outcomes. The probability of share repurchases that increase earnings per share (EPS) is sharply higher for firms that would have just missed the EPS forecast in the absence of the repurchase, when compared with firms that “just beat” the EPS forecast. We use this discontinuity to show that EPS-motivated repurchases are associated with reductions in employment and investment, and a decrease in cash holdings. Our evidence suggests that managers are willing to trade off investments and employment for stock repurchases that allow them to meet analyst EPS forecasts.